2018
DOI: 10.1101/471011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethanol Experience Enhances Glutamatergic Ventral Hippocampal Inputs to D1 Receptor-Expressing Medium Spiny Neurons in the Nucleus Accumbens Shell

Abstract: Nucleus accumbens dopamine D1 receptor-expressing medium spiny neurons (D1-MSNs) have been implicated in the formation of dependence to many drugs of abuse including alcohol. Previous studies have revealed that acute alcohol exposure suppresses glutamatergic signaling within the accumbens and repeated alcohol exposure enhances glutamatergic signaling. D1-MSNs receive glutamatergic input from several brain regions and it is not currently known how individual inputs onto D1-MSNs are altered by alcohol experience… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Recent work has identified that this pathway and its engagement of a feed-forward inhibitory circuit within the nucleus accumbens as important to a variety of behaviors (Scudder et al 2018;Yu et al 2017). The role of the vHC to accumbens pathway in ethanol drinking behavior is relatively unexplored but was recently shown to be influenced by ethanol dependence in the same mouse model used in the present studies (Kircher et al 2019). Thus, future work will focus on the ventral hippocampal to accumbens pathway and the role it plays in driving excessive drinking in ethanol dependence.…”
Section: Discussionmentioning
confidence: 77%
“…Recent work has identified that this pathway and its engagement of a feed-forward inhibitory circuit within the nucleus accumbens as important to a variety of behaviors (Scudder et al 2018;Yu et al 2017). The role of the vHC to accumbens pathway in ethanol drinking behavior is relatively unexplored but was recently shown to be influenced by ethanol dependence in the same mouse model used in the present studies (Kircher et al 2019). Thus, future work will focus on the ventral hippocampal to accumbens pathway and the role it plays in driving excessive drinking in ethanol dependence.…”
Section: Discussionmentioning
confidence: 77%
“…For clinical validation of these findings, we employed a double blind, placebo-controlled study in non-treatment seeking individuals with AUD and found that oral apremilast was effective at reducing the number of daily drinks consumed. Moreover, we identified that apremilast's effects at the level of the accumbens as important for regulating binge-like drinking and for regulating activity in a neural circuit relevant to alcohol-related behaviors 47,48 . Taken together, this collaborative set of studies from 5 independent laboratories and universities highlights apremilast as a powerful AUD treatment option and further identifies mechanisms by which apremilast may reduce harmful alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%